Evaluation of non-microbial salivary caries activity parameters and salivary biochemical indicators in predicting dental caries - Kaur, A; Kwatra, KS; Kamboj, P (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2012)
The aim of the present study was the evaluation of non-microbial salivary caries activity parameters and salivary biochemical indicators in predicting dental caries. The present study was carried out on 60 children, aged 4-6 years, selected from the schools of Panchkula district, Haryana, on the basis of their caries status. Level of hydration, flow rate, pH, buffering capacity, relative viscosity, calcium, phosphorus and alkaline phosphatase levels in caries-free and caries-active children were evaluated. Results showed that 90% of subjects in the caries-free group and 30% of subjects in the caries-active group had normal level of hydration value of less than 60 s and the difference was found to be statistically very highly significant. Normal flow rate of stimulated saliva was found in 90% of the subjects in caries-free group and 33.3% subjects in the caries active group and difference was found to be statistically very highly significant. Adequate salivary pH was found in 100% subjects in caries-free group and 30% in caries-active group and the difference was statistically very highly significant. To conclude, within limitations of this study, it became clear that normal level of hydration and higher values for flow rate, pH, buffering capacity of saliva lead to good oral health and a reduced caries occurrence. Increased salivary viscosity plays a role in increasing caries incidence. Salivary biochemical indicators like calcium, phosphorus and alkaline phosphatase also play their respective role in determining caries susceptibility of an individual. These salivary parameters can be used as diagnostic tool for caries risk assessment.